The regulatory impact of serine/threonine-specific protein phosphorylation among cyanobacteria - Barske, Thomas; Hagemann, Martin (Frontiers in Plant Science, 2025)
Cyanobacteria are the only prokaryotes capable of performing oxygenic photosynthesis. To thrive under environmental fluctuations, photosynthesis and metabolic activities needs to be adjusted. Previous studies showed that the acclimation of primary carbon metabolism to fluctuating carbon/nitrogen levels is mainly regulated at post-transcriptional level including diverse posttranslational modifications (PTMs). Protein phosphorylation is regarded as main PTM in the sensing and balancing metabolic changes. In this review we aim to summarize the knowledge on serine/threonine-specific protein phosphorylation among cyanobacteria. Phosphoproteome studies identified several hundred phosphoproteins bearing many more specific phosphorylation sites. On the other hand, only relatively few serine/threonine-specific protein kinases were annotated in cyanobacterial genomes, for example 12 in the model cyanobacterium Synechocystis sp. PCC 6803. Systematic mutation of the kinase-encoding genes revealed first insights into their specific functions and substrates. Future research is needed to address how a limited number of protein kinases can specifically modify hundreds of phosphoproteins and to uncover their roles in the regulatory networks of cyanobacterial metabolism.